Molecular testing prognostic of low risk in epithelioid uveal melanoma in a child. Issue 3 (3rd January 2013) - Dimaras, Helen; Parulekar, Manoj Vijay; Kwok, Grace; Simpson, E Rand; Ali, Asim; Halliday, William; Shago, Mary; Harbour, J William; Héon, Elise; Gallie, Brenda L; Chan, Helen S L
Abstract : Aims: To characterise a histologically unusual paediatric uveal melanoma by gene expression and karyotypic profiling and assess prognosis. Methods: The tumour was studied by histopathology, karyotype analysis, single nucleotide polymorphism and gene expression profile analysis for correlation with clinical outcome. Results: The tumour had predominantly epithelioid histology. Karyotype analysis showed none of the poor prognosis features normally associated with uveal melanoma. single nucleotide polymorphism analysis revealed no imbalance at chromosome 3. Gene expression profiling indicated low risk disease. Conclusions: We report a child remaining relapse-free 6 years after diagnosis of a very rare uveal melanoma, with poor prognosis epithelioid histology, but gene expression profiling that accurately predicted low risk disease.